Medicare Access and CHIP Reauthorization Act and Rural Hospitals. Issue 3 (July 2019) - Kelley, Erica; Lipscomb, Rhea; Valdez, Jennifer; Patil, Nitesh; Coustasse, Alberto
Abstract : The cost of health care within the United States has continued to increase, whereas the quality of patient care has generally decreased in some areas. With the continued use of Medicare's former physician reimbursement algorithm, termed sustainable growth rate, national expenditures within the United States have been expected to increase 5.6% annually. To modernize the delivery and financing of care, Congress has introduced the Medicare Access and CHIP Reauthorization Act of 2015 (MACRA), which has permanently eliminated and replaced the sustainable growth rate. The purpose of this study was to review MACRA and its implementation to determine how it would financially impact rural hospitals. Two reimbursement pathways have been created for physicians under the MACRA. In addition, the financing and competition among facilities created by the act have been expected to impact physicians and health care organizations. Rural hospitals have been set to receive reduced government reimbursements and have been predicted to compete poorly with larger hospitals and health care corporations. Furthermore, the payment tracks available through the act have been projected to impact solo and small practice physicians negatively.